2019
DOI: 10.1556/2060.106.2019.04
|View full text |Cite
|
Sign up to set email alerts
|

The role of astrocytes on the effects of exercise on episodic memory function

Abstract: This review discusses the potential role that glial cells may play in influencing the relationship between exercise and episodic memory function. A narrative review methodology is employed. Herein, the different types of glial cells, their implications in subserving episodic memory function, and how exercise can modulate glial cell activity, particularly astrocyte functionality, are discussed. Although additional experimental work is needed, astrocytes appear to play an important role in the exercise–memory in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 42 publications
2
34
0
1
Order By: Relevance
“…Specifically, the hippocampi are more enriched with astrocytes than the FC [50], and it was shown that FASN is expressed by glial cells but not by neurons [51]. Physical activity can also increase the number of astrocytes [52] and induce their biochemical reprograming [53]. Thus, astrocytes are likely to contribute to metabolic adaptation to energetic stress and distinct responses induced in the hippocampi and the FC during exercise as observed in our study.…”
Section: Discussionsupporting
confidence: 57%
“…Specifically, the hippocampi are more enriched with astrocytes than the FC [50], and it was shown that FASN is expressed by glial cells but not by neurons [51]. Physical activity can also increase the number of astrocytes [52] and induce their biochemical reprograming [53]. Thus, astrocytes are likely to contribute to metabolic adaptation to energetic stress and distinct responses induced in the hippocampi and the FC during exercise as observed in our study.…”
Section: Discussionsupporting
confidence: 57%
“…Specifically, the hippocampi are more enriched with astrocytes than the FC [50], and it was shown that FAS is expressed by glial cells but not by neurons [51]. Physical activity can also increase the number of astrocytes [52] and induce their biochemical reprograming [53]. Thus, astrocytes are likely to contribute to metabolic adaptation to energetic stress and distinct responses induced in the hippocampi and the FC during exercise as observed in our study.…”
Section: Discussionsupporting
confidence: 58%
“…We have extensively demonstrated that acute exercise [1,2], particularly high-intensity exercise [3], can enhance memory function, including episodic memory [4,5] and working memory capacity [6]. Mechanisms of this effect can be found elsewhere [7,8,9,10,11], and include, for example, increased neuronal excitability in key memory-related brain structures (e.g., hippocampus) [12]. What has been considerably less investigated, however, is whether acute exercise can effectuate intentional forgetting.…”
Section: Introductionmentioning
confidence: 99%